The history of stellar mass in the most massive galaxies at z < 3.5 - Mundy, Carl J. (2017)
Observations have shown that galaxies have undergone intense transformations over the past 11 Gyr, increasing both their size and stellar mass in the process. Uncovering and understanding the mechanisms behind such changes remains one of the aims of modern astronomy. This Thesis presents an investigation into two mechanisms - star-formation and galaxy mergers - which may be responsible for these observed changes. This is achieved through the analyses of several publicly a available semi-analytic models of galaxy formation and evolution, combined with a large sample of approximately 350,000 galaxies at 0.005< z <3.5. Firstly, a comprehensive study is detailed comparing two methods which aim to connect galaxies across cosmic time, to ascertain the best method of tracing the true evolution of a galaxy population's most fundamental properties across large redshift ranges. This is done using a suite of semi-analytic models and selecting galaxies at either a constant stellar mass, or a constant cumulative number density ranked by stellar mass. It is found that the latter selection is better at tracing the true evolution in stellar mass and star-formation rate of a galaxy population, both forwards and backwards in time, compared to the former method. The method allows these properties to be recovered within a factor of 2-3 across a redshift range of 0< z <3, with the systematic o set proportional to the redshift range probed. This contrasts with a constant stellar mass selection - used throughout the literature - which often overestimates these physical properties by up to a factor of ~20, depending on the mass range probed. Secondly, this Thesis introduces a method allowing for the measurement of the close-pair fraction for galaxies selected by stellar mass from a flux-limited survey. Previous measurements of the merger fraction suffered from small volumes or uncertain statistical corrections for projected close-pairs of galaxies. The method presented herein, adapted from that presented in Lopez-Sanjuan et al. (2015), uses the full redshift probability distribution to measure the pair fraction of galaxies at >1010M, and at a constant cumulative number density of 10-4 Mpc-3, representing the best constraints on the pair fraction at z < 3.5 to date. Major and minor merger pair fractions approximately a factor of ~ 2 smaller than previous works are found and subsequently converted to merger rates. The major merger rate is found to be similar for galaxies at >1011Mand>1010M, while the minor merger rate is larger for the most massive galaxies by a factor of ~ 2. Finally, the relative role of galaxy mergers and star-formation in the build up of stellar mass is explored. Using star-formation rate estimates, a statistical estimation of the star-formation rate density and the merger accretion rate density of stellar mass-selected samples are compared and contrasted. From this analysis, it is found that star-formation remained the dominant source of stellar mass growth in massive galaxies until z ~ 0.5, with major merger becoming comparable in more recent times and minor mergers a factor of ~ 10 smaller even today. Furthermore, simple virial arguments are used to show that major and minor mergers are likely not the dominant mechanism in the size evolution of massive galaxies at z < 3.5, increasing their sizes by a factor of ~ 1.6 at most. In summary, the results presented in this Thesis explore the stellar mass, star-formation and size evolution of massive galaxies over the past 11 Gyr, and shed new light on the mechanisms responsible. By taking advantage of the latest wide-area, deep surveys, the largest sample of galaxies is used to constrain the merger histories of massive galaxies and infer their role in the evolution of massive galaxies in a consistent manner.